The arraignment and conviction of Sr VValter Rawleigh, at the Kings Bench-barre at Winchester. on the 17. of November. 1603. Before the right Honorable the Earle of Suffolke, Lord Chamberline, the Earle of Devon-shire, Lord Henry Howard, Lord Cecill, Lord Wotton, Sir John Stanhope Lord Chiefe Justice of the Common-pleas, Popham and Andrewes, Justice Gaudy, Justice Warberton, Sir William Wade, commissioners. / Coppied by Sir Tho: Overbury.
Summary goes here